Psychotherapeutic support for persons with vascular dementia suffering from non-cognitive psychopathological symptoms of non-psychotic level - Zlobin, O. O. (My University, 2020)
Introduction. In addition to cognitive deficit, the presence of a dementing process of vascular origin leads to changes in the patient’s personality, as well as in his character. Persons with vascular dementia always have non-cognitive disease manifestations of non-psychotic level. Non-psychotic psychopathological symptoms can lead to a significant deterioration of the well-being and quality of life of patients with vascular dementia, and therefore should be taken into account when drawing up a plan for treatment and rehabilitation of such patients. Psychotherapy interventions play the most important role in management of patients with vascular dementia. The aim of the study: to develop a targeted model of psychotherapeutic support based on the selective correction of non-cognitive psychopathological symptoms of non-psychotic level in patients with vascular dementia. Materials and methods: The study was carried out on 80 patients with vascular dementia with different localization of the lesion. The average age of the patients was 68.6 years. All persons included in the contingent of the study demonstrated non-cognitive psychopathological symptoms of non-psychotic level. Results. Recommendations for psychocorrection of maladaptive non-cognitive pathopsychological symptomatology of non-psychotic level in persons with vascular dementia have been developed. For each of these symptoms, congruent vectors, mechanisms, and methods of psychotherapeutic correction were identified and described. The basic vector for minimizing and eliminating depression in patients with vascular dementia aimed at shifting the mode of emotional experiences from the negative spectrum to the positive or at least neutral. The basic vector for minimizing and eliminating anxiety in patients with vascular dementia aimed at shifting attention from stressful factors to sanogenic, emotionally neutral stimuli. The basic vector for minimizing and eliminating apathy in patients with vascular dementia aimed at activation of mental processes and restoration of a minimum acceptable level of emotional response. The basic vector for minimizing and eliminating irritability in patients with vascular dementia aimed at increasing the threshold of negative emotional response to environmental stimuli. The basic vector for minimizing and eliminating emotion incontinence in patients with vascular dementia aimed at restoring the ability to control external manifestations of internal feelings.
Keywords: vascular dementia; psychotherapy; affective symptoms; rehabilitation; geriatric psychiatry